Pengembangan Media Pembelajaran Fisika Berbasis IoT dan Pengaruhnya Terhadap Kemampuan Berpikir Kritis Siswa - Matsun matsun; Soka Hadiati; Dwi Fajar Saputri (Postgraduate, University of Mataram, 2022)
The implementation of an independent curriculum by the government has an impact on the world of education. Classroom learning requires teachers to be active in developing project-based learning. The development of IoT (Internet of Things)-based physics learning media and its effect on student's critical thinking skills is the goal of this research. The research method used is research and development (R&D) with the Four-D model with the steps of Define, Design, Develop, and Disseminate. The results of the development of IoT-based physics learning media show that the assessment of experts (material and media experts) is in a very Worthy category. The results of the questionnaire response of 70 students also rated this media